Running Water in India's Cities : A Review of Five Recent Public-Private Partnership Initiatives - World Bank (Washington, DC, 2014)
India is home to more than 370 million people in urban areas. Historically, almost all water supply provision has been managed by the public sector through municipal or state-level departments or parastatals. Benchmarking initiatives show that coverage through piped water supply ranges between 55 percent and 89 percent in urban areas. Per capita availability is fairly high, at 90 to 120 liters per day, but no city yet offers continuous water supply. Daily supply averages four hours, with many cities alternating supply every other day. These challenges occur in a context of weak management systems and little data on existing assets, which makes it difficult to assess investment needs and time lines to improve service levels and operational efficiencies. While investment requirements are likely to be significant, it is recognized that investments alone will not be effective unless the country simultaneously addresses related issues such as complex and fragmented institutions with little accountability; lack of capacity to run utilities efficiently and meet performance standards; weak commercial orientation; interference in utility operations by external entities; and the absence of a regulatory framework focused on customer service and financial sustainability. In response to social issues, all contracts have proactively provided for service delivery options to consumers as well as tariff concessions (bulk supply to poor neighborhoods, fortnightly payment options, special tariff for group connections, and so forth). It will also be useful to explicitly state the subsidy that the city will bear for connecting poor consumers to the network. Explicit arrangements in the contract will allay apprehensions of urban poor as well as encourage the operator to connect the poor.